RE-EXAMINATION OF BERLINITE (AIPO4) FROM THE CIOCLOVINA CAVE, ROMANIA - Onac B.P.; Effenberger H.S. (My University, 2007)
Berlinite is a mineral indicative of high-temperature formation and, therefore, it would not be expected to be present in a sedimentary environment. In this study, we review the characteristics of a berlinite-bearing deposit and present a single-crystal structure investigation based on X-ray data: the refinement converged at R1(F) = 0.0276, wR2(F2) = 0.0657 for 677 reflections (2θMoKα ≤ 70°) and 31 variables in space-group P3121 [a = 4.9458(10), c = 10.9526(20) Å, V = 232.0 Å3, Z = 3 {AlPO4}]. The average bond distances within the two crystallographically unique TO4 tetrahedra are 1.734 and 1.526 Å, respectively. From the scattering power at these T sites and the stereochemistry, the presence of an AlO4 tetrahedron linked to a PO4 tetrahedron is established. Consequently, the sample from Cioclovina Cave is verified as AlPO4 (modification berlinite), reconfirming the first description of this mineral from a sedimentary occurrence, which underwent an obvious natural heating process.
Keywords: BERLINITE; CAVE MINERALS; CIOCLOVINA CAVE; ROMANIA